THE EFFECTS OF HUMIC ACID ON ABOVE-GROUND PARTS OF BROAD BEAN (Vicia faba L.) SEEDLINGS UNDER AL(3+) TOXICITY - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2011)
This study has emphasized the effect of humic acid (HA) on the growth, development and uptake of certain nutrients in broad bean (Vicia faba L. cv. ERESEN 87) seedlings grown in aluminum-contaminated compost in pots during 2007/2009 under greenhouse conditions. Concentrations of Hoagland-Arnon (HO) solutions were prepared with 50 and 100 mu M AlCl3 only for controls of HO, and additionally with HA for experimental treatments. The application of HA 50 solution caused a significant increase (compared to controls) in plant height (PH-cm), number of leaves (NL-No), leaf area (LA-cm(2)), fresh weights of leaf (LFW-g), stem fresh weight (SFW-g), dry weights of leaves (LDW-g) and stem dry weight (SDW-g). HA 100 caused significant increases in (NL-No), (LFW-g) (LDW-g), and all related growth parameters increased, but were not significantly different from HO-treated ones in broad bean seedlings. Flame photometry (FP) and inductively coupled plasma atomic emission spectrometry (ICP-AES) analyses of nutrients indicated that the concentration of potassium was higher than that of all other nutrients. HA caused reductions in Al3+, Cu2+ and Zn2+ contents of the above-ground parts of organs in both HA treatments (50 and 100 RM), but only being significant for Al3+ content in HA50. Mn2+, Fe3+, Na+, K+ and Ca2+ levels increased in both concentrations, however, results were only significant for Na+ and Ca2+ in HA100, and for K+ in both HA50 and HA100 treatments. So, it can be suggested that HA contributes to the development of above-ground parts of broad bean seedlings effectively by balancing the nutrients tested in the current experiment as well as decreasing the toxic effects of Al3+.
Keywords: Humic acid; nutrients; broad bean (Vicia faba L.); aluminum toxicity; ALUMINUM TOXICITY; ZINC ADSORPTION; GROWTH; TOLERANCE; CALCIUM; SUBSTANCES; NUTRITION; TOMATO; RESISTANCE; PHYSIOLOGY